Tourism Talk on Wheels: Code-Mixing as a Communicative Strategy in Jinrikisha-Based Tourist Communication - Harisal Harisal; Imelda Imelda; Indra Mayanti Noer; Heriyanto Heriyanto (Vocational College of Diponegoro University, 2026)
Communication between the shafu (rickshaw pullers) and tourists riding the jinrikisha often involves the occurrence of code-mixing. This study investigates code-mixing as an integral component of jinrikisha-based tourist communication, with a particular focus on the informal yet impactful role of the shafu as linguistic and cultural mediators. Situated within the sociolinguistic framework of tourism discourse, this research adopts a qualitative-descriptive methodology to explore the communication strategies employed by the shafu in the jinrikisha tourism industry. Special attention is given to recorded instances of code-mixing in order to analyze the multilingual strategies used to negotiate meaning, build rapport, and enhance the overall tourist experience. The findings reveal that the linguistic adaptability demonstrated by the shafu reflects a form of localized communicative competence shaped by the demands of global tourism and context-specific language ideologies. The utterances produced by the shafu are not random or incidental; rather, they are shaped by repeated interactions with tourists, the desire to be understood, and the necessity to appear competent and welcoming within a competitive tourism market.